THEORETICAL PRINCIPLES OF ORGANIZATION IMPROVEMENT ADMINISTRATIVE WORK AT THE ENTERPRISE - Мороз, Людмила (Modern engineering and innovative technologies, 2023)
On the basis of management functions, general management functions of management of any rank and sphere of production are highlighted, and the basic principles of improving the organization of operational production management are considered, taking into